2019
DOI: 10.3390/app9061142
|View full text |Cite
|
Sign up to set email alerts
|

Design and Kinematic Control of the Cable-Driven Hyper-Redundant Manipulator for Potential Underwater Applications

Abstract: Underwater manipulators are important robotic tools in the exploration of the ocean environment. Up to now, most existing underwater manipulators are rigid and with fixed 5 or 7 degrees of freedom (DOF), which may not be very suitable for some complicated underwater scenarios (e.g., pipe networks, narrow deep cavities, etc.). The biomimetic concept of muscles and tendons is also considered as continuum manipulators, but load capacity and operation accuracy are their essential drawbacks and thus limit their pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…However, these continuum robots can be controlled only by means of a finite number of DOF, which reduces the set of solutions. In this paper, many research works have been proposed in literature to accomplish this purpose [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…However, these continuum robots can be controlled only by means of a finite number of DOF, which reduces the set of solutions. In this paper, many research works have been proposed in literature to accomplish this purpose [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Symbols utilized in this study are summarized in Table A.1-A. 4, and acronyms utilized in this study are concluded in Table A. 5.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…High flexibility of avoiding obstacles, good loading capacity, and easy maintenance should be taken into consideration for the structural design of robotic arms to satisfy the requirement of tasks under complicated working circumstances. A snakelike continuum manipulator with redundant DOF inspired by the biomimetic structure of vertebrate limbs has attracted increasing attention of researchers but limited to the drawbacks such as slight load capacity, imprecisely controlled and limited measurements, alleviated after the cable-driven technique introduced [3].…”
Section: Introductionmentioning
confidence: 99%